Preventive use of low molecular weight heparin in portal vein system thrombosis after splenectomy without portal hypertension. Issue 12 (December 2022) - Wei, Qiang; Mei, Shengmin; Fu, Zhifei; Wang, Xiaodong; Han, Chengzuo; Chen, Jun; Liu, Peng; Chen, Bin; Fang, Xin; Jia, Changku; Zheng, Shusen; Xu, Xiao
Abstract: Background/aim: Portal vein system thrombosis (PVST) is a serious complication after splenectomy, and many researches focus on how to prevent PVST these years. The current study aimed to explore an effectively method to prevent PVST occur after splenectomy. Methods: Records of patients performed with splenectomy from January 2018 to December 2020 were reviewed. Clinical parameters, including patient history, physical examination, and the results of laboratory investigations, were analyzed. Results: One hundred and eighty patients (127 females) were included. Twenty-four patients were confirmed PVST by Color Doppler ultrasonography and CTA (thrombus group) and the others were not (non-thrombus group). One hundred and twenty patients were performed with laparoscopic splenectomy (LS) and 53 were open splenectomy (OS). Seventeen PVST were found in LS patients and 7 PVST were found in OS patients (P = 0.974). The average time of thrombosis was 4.48 ± 2.9 days after operation. The proportion of postoperative preventive use of low molecular weight heparin (LMWH) in non-thrombus group was higher than that in thrombus group (27.6% vs. 8.3%, P = 0.045). Compared with the non-thrombus group, the thrombus group showed significantly higher serum alanine transaminase (ALT) and aspartate transaminase (AST) 7 days after splenectomy (79.67 ± 39.1 U/L vs. 29.34 ± 2.5 U/L, P = 0.001; 192.4 ± 145.8 U/L vs. 30.54 ± 3.0 U/L, P < 0.001). Conclusion: Laparoscopic splenectomy does not seem to increase the occurrence of PVST in patients without portal hypertension. Early postoperative preventive use of LMWH after splenectomy may prevent the formation of PVST. Abstract : Portal vein; Thrombosis; Splenectomy; Heparin; Portal hypertension.